Cultural variation in the SES-gender interaction in student achievement - Eriksson, Kimmo; Lindvall, Jannika (Frontiers in Psychology, 2023)
Introduction Is the socioeconomic gap in academic achievement larger among boys than girls? Several scholars have proposed such an interaction between socioeconomic status (SES) and gender. Prior empirical studies have yielded mixed evidence, but they have been conducted almost exclusively in Western countries. Here we propose the hypothesis that the SES-gender interaction is stronger in less gender-equal societies. Methods We estimated the SES-gender interaction in 36 countries using data from two international large-scale assessments (PIRLS and TIMSS). The degree of gender equality was measured by the Global Gender Gap Index. Results Consistent with the hypothesis, the SES-gender interaction was stronger in societies with less gender equality. Discussion Our findings suggest that cultural factors determine how the socioeconomic achievement gap differs between boys and girls.